Disruption of the TSLP-TSLPR-LAP signaling between epithelial and dendritic cells through hyperlipidemia contributes to regulatory T-Cell defects in atherosclerotic mice. Issue 2 (February 2015) - Yu, Kunwu; Dong, Qian; Mao, Xiaobo; Meng, Kai; Zhao, Xiaoqi; Ji, Qingwei; Wu, Bangwei; Zhong, Yucheng; Zhu, Zhengfeng; Liu, Yuzhou; Zhang, Wei; Tony, Hasahya; et al.
Abstract: Regulatory T-Cells (Tregs) play a protective role against the development of atherosclerosis. Moreover, thymic stromal lymphopoietin (TSLP)/thymic stromal lymphopoietin receptor (TSLPR) signaling in myeloid dendritic cells (DCs) promote Treg differentiation. Here, we examined the potential role of TSLP/TSLPR on Treg homeostasis in atherosclerosis. The frequencies of both latency-associated peptide (LAP) + and Foxp3 + Tregs were reduced in the thymus and spleen of ApoE −/− mice compared with C57BL/6 mice, and this effect was associated with decreased thymic output. The tolerogenic function of DCs obtained from ApoE −/− mice was compromised compared with those from C57BL/6 mice. The expression of TSLP and TSLPR was also inhibited in ApoE −/− mice. In addition, we found that ox-LDL attenuated TSLP expression in cultured thymic epithelial cells (TECs) through the activation of retinoid X receptor alpha (RXRA) and IL-1β and decreased LAP and PD-L1 expression in oxLDL-activated DCs while both were up-regulated in TSLP-activated DCs. We also observed that the TSLP-DCs mediated differentiation of Tregs was abrogated through LAP neutralization. Furthermore, TSLP injection rescued Treg defects in ApoE −/− mice. These findings suggest that Treg defects in ApoE −/− mice might partially be attributed to the disruption of TSLP-TSLPR-LAP signaling in epithelial cells (ECs) and DCs. Highlights: The number and function of Regulatory T cells were decreased and impaired in immune organs of atherosclerotic mice. The tolerogenic function of dendritic cells from atherosclerotic mice was compromised. The expression of TSLP and TSLPR was inhibited in atherosclerotic mice. Ox-LDL attenuated TSLP expression in cultured TECs and disrupted tolerogenic function of cultured DCs. TSLP could rectify regulatory T cell defects in atherosclerotic mice.